PENYULUHAN BAHAYA NARKOBA DAN STRATEGI PENCEGAHANNYA DI DESA PANTAI BAKTI - Muhammad Ihsan Zainuddin; Acep Mulyadi; Agus Supriyanto (An-Nizam, 2023)
In Indonesia, the drug problem is still an urgent and complicated problem. This problem has gotten worse in the last ten years. This counseling is motivated by the many problems of drug abuse in adolescents. This situation encourages students to take preventive measures, education to overcome the problem of drug abuse and drug abuse among adolescents is not increasing. One of the main reasons why young people use drugs is the lifestyle of the middle class of society. whose aim was to be hairless, which resulted in the smuggling of narcotics to more and more young people. and drug addiction. The result of this activity is that SMPN 1 ATAP students understand how to manage their medication so they can work to protect themselves from things that can lead to abuse.